Pengaruh Peranan Orang Tua terhadap Perkembangan Bahasa dan Bicara Anak Usia Dini - Della Mustika Rahayu (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
The world of play is the world of early childhood by playing children interacting with their playmates using tools, namely language, with the language of the child being able to express the contents of their hearts and minds so that other people are able to understand what the child means. We can know that early language development in children begins at birth. Children's language development is intended to enable children to communicate verbally with the surrounding environment so that parents and adults can provide optimal language stimulation in accordance with the stages of early childhood development. Environmental impact and parenting are very influential so that it becomes the cause of children's language development thus language development will be better if the child gets a stimulus and guidance from his own parents, many things parents can do such as developing aspects of language development through storytelling, playing with children, communicate actively with children because first and foremost education is the family environment.